Bamboo Control - Jason A. Ferrell; Mark Czarnota; Kenneth Langeland (EDIS)
SS-AGR-75, a 2-page fact sheet by Jason Ferrell, Mark Czarnota, and Ken Langeland, describes the management practices for controlling invasive, non-native varieties of bamboo. Published by the UF Department of Agronomy, October 2006.